Three essays on practical implementations of real money concepts - Owolabi,Yusuf Muhammad-Bashir (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
August 2007 financial crisis, the worst after the great depression, has prompted the world leaders at to call for overhauling of the world monetary system as was done at the Bretton wood. This has led economists to suggest different monetary concept. Even the head of largest development institution in the world, World Bank, Robert Zoellick, once called for the backing of fiat currency by gold. This study has identified three of such monetary concepts proposed by people to solve or prevent future financial crisis and studied the practical implications of their implementation. The three studied concepts are: gold standard, gold currency and business to business barter trade. The first essay looked efficient trade matrix and gold reserve requirement for intra- commodity trade in selected countries of the organization of Islamic cooperation countries. The second essay investigated the determinants of gold dinar (gold currency) in Kelantan, Malaysia and the last essay studied the operationalization and acceptance of barter transaction in Malaysia. This thesis is the first of its kind to have brought these three issues together in a study. It has employed distinct technique in each of the essays. The first essay employed non-linear mathematical programming to determine trade optimization and the quantity of gold needed to settle the net payment in bilateral and multilateral trade arrangements among these countries. The second essay used structural equation modeling techniques to uncover the determinants of adoption of gold dinar in Kelantan Malaysia based on the concepts of adoption of innovation from the theories of acceptance of innovation in the literature. The last essay on operationalization and acceptance of barter used mixed methodology to answer its objectives. These are qualitative and quantitative methods of data analysis. The qualitative aspect employed interview and content analysis for in-depth understanding of the operation of barter, while in quantitative part, partial least square technique was used for the structural path analysis of the proposed model of acceptability of barter. This allowed for the use of small sample and highly skewed data. Based on year 2008 commodity data for the five selected countries and five products taken from the United Nation Commodity Trade Statistics, efficient trade matrix for these countries for the products and the net gold requirement for settlement were computed. It was discovered that the amount of gold needed for commodity trade decrease from gross through bilateral to multilateral arrangement. The second essay applied structural equation modeling to a cross-sectional data collected from gold users in Kelantan to obtain the measurement and structural model from the sample. Thus two outcomes were achieved from the study. First is the determination of the components of gold dinar adoption from the measurement model and the second outcome is the uncovering of factors that have significant impacts on the adoption of gold dinar from the structural model. The data for the third essays came from both in-depth interview of the representative of business to business barter trade in Malaysia and content analysis of the company on one hand, and survey questionnaire administered to the client (participants) of business to business transaction in Malaysia. The essay employed mixed methodology to explore the operationalization and user's acceptance of business to business barter transaction in Malaysia. The qualitative methods used to explore the operation of barter trade in Malaysia are in-depth interview, observation and document analysis. Descriptive statistics was used to profile the socio-economic characteristics of barter trade members, while PLS technique was employed to analyze the hypotheses of user's acceptance of barter exchange in Malaysia. The data was found to fit the hypothesized model, with most of the structural link path coefficient statistically significant.